“Lost All Hope in Government”: Learned Helplessness of Professionals Working in Specialised Education Settings in England During COVID-19 - Mahmud, Arif; Castro-Kemp, Susana (Frontiers in Education, 2022)
Covid-19 has had substantial impact on children’s educational experiences, with schools and educators facing numerous challenges in adapting to the new reality of distance learning and/or social distancing. However, previous literature mostly focuses on the experiences of families (including families of children with special educational needs and disabilities [SEND]) and those of teachers, predominantly working in mainstream settings. This paper aims to gauge the perspectives of educators working in specialised education settings that serve children with SEND in England on how they experienced working in those settings during the pandemic, including in during lockdown. A mixed (qualitative and quantitative) online survey was responded to by 93 educators. Responses denote emotionally charged views and a sense of learned helplessness. Most special schools were unable to implement social distancing measures in full or provide adequate protective equipment. The main challenges the respondents mentioned included lack of guidance from Governmental authorities, staff shortages, work overload, challenging relationship with parents and issues in meeting children’s complex needs. Professionals working for less than 3 years in a special school were more likely to say they would change jobs if they could, when compared to professionals with more years of experience. No effects of demographic characteristics were found in relation to professionals’ ratings of their own wellbeing during lockdown. Findings are discussed in light of the concept of learned helplessness and suggest that there is a need to reform provision in special schools in England to foster its sustainability and positive outcomes for children.